Relationships Between the Body Image and Physical Activity on Spanish Adolescents - Dorado-Guzmán, Manuel (UMA Editorial, 2016)
A distortion of body image should be related with some body composition- related disorders, which has a behavioral etiology, mainly for adolescents. The body shape self-perception should one important risk factor, and some surveys have suggested that physical activity (PA) would be contributor to promote a better body self-perception. However, there is not enough evidence about what is the relationship between body composition, different patterns of PA and body shape in adolescents. PURPOSE: To explore the relationship between body image perception, body composition and PA in Spanish adolescents. METHODS: 829 healthy students accepted and were authorized to participate in this study (405 boys and 424 girls; 14.3 ±1.2 years; body mass index, 20.7 4.0 kg/m2). Body composition was estimated using bioelectric impedance and anthropometry. Body shape was assessed with Figure Rating Scale (FRS) and body satisfaction with Body Shape Questionnaire (BSQ), Daily PA and out-of-school PA (OSSP) were recorded by a validated physical activity questionnaire for Spanish adult children (PAQ-A). Pearson’s correlation coefficient was used to explore the relationships between variables. Independent sample T-test was carried out to compare body image perception between adolescents with and without OSSP. RESULTS: A significant relationship between body image and Body Mass Index (BMI) was found (rho=0.653, p<0.001). Significant relationship was found between BSQ score and PA (rho =0.142, p<0.001). BSQ score was significantly different between adolescents with OSSP and without NOSSP (53.6 ±24.4 vs. 61.7 ±29.5). CONCLUSION: Our main finding was that adolescents, who reported OSSP showed an improved body shape perception. However, PA was related with BSQ score. Also, in accordance with other studies with adolescent, the higher BMI higher BSQ score. These results suggest that some characteristics of the OSSP can help to improve body self-perception; however more research is necessary in order to clarify this relationship.
Keywords: Adolescentes; Adolescentes -- Psicología; Body image; Adolescents; Tesis doctoral; Body composition; Physical Activity